The phenotypic spectrum of progressive supranuclear palsy: A retrospective multicenter study of 100 definite cases - Respondek, Gesine; Stamelou, Maria; Kurz, Carolin; Ferguson, Leslie W.; Rajput, Alexander; Chiu, Wan Zheng; van Swieten, John C.; Troakes, Claire; al Sarraj, Safa; Gelpi, Ellen; Gaig, Carles; Tolosa, Eduardo; et al. (Movement disorders, 2014)
The phenotypic variability of progressive supranuclear palsy (PSP) may account for its frequent misdiagnosis, in particular in early stages of the disease. However, large multicenter studies to define the frequency and natural history of PSP phenotypes are missing. In a cohort of 100 autopsy‐confirmed patients we studied the phenotypic spectrum of PSP by retrospective chart review. Patients were derived from five brain banks with expertise in neurodegenerative disorders with referrals from multiple academic hospitals. The clinical characteristics of the 100 cases showed remarkable heterogeneity. Most strikingly, only 24% of cases presented as Richardson's Syndrome (RS), and more than half of the cases either showed overlapping features of several predescribed phenotypes, or features not fitting proposed classification criteria for PSP phenotypes. Classification of patients according to predominant clinical features in the first 2 years of the disease course allowed a more comprehensive description of the phenotypic spectrum. These predominance types differed significantly with regard to survival time and frequency of cognitive deficits. In summary, the phenotypic spectrum of PSP may be broader and more variable than previously described in single‐center studies. Thus, too strict clinical criteria defining distinct phenotypes may not reflect this variability. A more pragmatic clinical approach using predominance types could potentially be more helpful in the early recognition of and for making prognostic predictions for these patients. Given the limitations arising from the retrospective nature of this analysis, a systematic validation in a prospective cohort study is imperative. © 2014 International Parkinson and Movement Disorder Society